Does the mixing and placement regime affect the pH of Mineral Trioxide Aggregate? - TÜRKAYDIN, DİLEK; BAŞTÜRK, FATIMA BETÜL; GÜNDAY, MAHİR (My University, 2019)
Aim:The objective of this study was to measure in a laboratorysetting the pH of tooth coloured ProRoot MTA and MTAAngelus following various mixing and placement techniques,including mechanical mixing, manual mixing and indirect ultrasonicactivation.Materials and Method: Tooth coloured ProRoot MTA andWhite MTA Angelus were used. One gram of each powderwas mixed with a 0.34 g of distilled water that were allocatedto eight experimental groups, each containing three specimens.Four groups were prepared by mechanical mixing ofcapsules for 30 s at 4500 rpm the other four were mixed manually.Half of the specimens in each group were placed inmoulds using indirect ultrasonic activation. pH values wererecorded directly from within the freshly mixed material andwere analyzed using one-way ANOVA at a 0.05 level of significance.Results: No significant difference in pH was found betweenthe mixing and placement techniques or the materials tested.The highest pH value recorded was in the ProRoot group thatwas mixed manually and placed ultrasonically (11.64). TheAngelus group, which was mixed manually without an ultrasonicagitation, had the lowest pH values (10.42).Conclusion: Mechanical mixing and ultrasonication conferredno significant disadvantage in terms of the initial pH ofthe material. Since mechanical agitation of encapsulated cementsprovides more consistent mixes, it might be possible touse this technique combined with ultrasonic agitation as analternative to manual mixing, both in clinical and in laboratoryconditions, in order to achieve standardization of the materialso as to enhance its properties.

Amaç: ProRoot MTA ve MTA Angelus'un mekanik ve elle karıştırma teknikleriyle karıştırılıp, indirekt ultrasonik aktivasyon ile yerleştirilmesinin materyalin pH değerleri üzerindeki etkisini in vitro olarak incelemektir. Gereç ve Yöntem: Beyaz ProRoot MTA ve beyaz MTA-Angelus kullanılmıştır. Bir gramlık toza 0,34 g distile su eklenmiş ve sekiz grup hazırlanmıştır. Grupların yarısı, kapsüllere yerleştirilerek 4500 rpm hızda 30 sn boyunca karıştırılmış, diğer yarısı ise elle karıştırılmıştır. Hazırlanan bu karışımların yarısına indirekt ultrasonik aktivasyon uygulanmıştır. Numunelerin pH değerleri karışım hazırlandıktan hemen sonra ölçülmüş ve değerler one-way ANOVA ile 0,05 anlamlılık düzeyinde değerlendirilmiştir. Bulgular: Test edilen materyaller bazında, karıştırma ve yerleştirme tekniklerinin arasında herhangi bir anlamlı fark bulunamamıştır. En yüksek pH değeri elle karıştırılıp ultrasonik aktivasyon uygulanan ProRoot grubunda (11,64), en düşük pH değeri ise elle karıştırılıp ultrasonik aktivasyon uygulanmayan MTA Angelus grubunda kaydedilmiştir (10,42). Sonuçlar: Mekanik karıştırma ve ultrasonik aktivasyon, mater yalin pH değeri üzerinde herhangi bir olumsuz etki göstermemiştir. Karıştırma ve yerleştirme teknikleri materyalin pH değerleri üzerinde herhangi bir etkiye sebep olmamıştır. Kapsüller içerisindeki simanların mekanik olarak karıştırılmasının daha tutarlı kıvamda karışımlar hazırladığı göz önünde bulundurulursa, bu tekniği ultrasonik aktivasyonla birlikte uygulamak hem klinik hem de laboratuvar koşulları altında standardizasyonun sağlanması açısından bir alternatif olarak düşünülmelidir.
Karıştırma ve yerleştirme teknikleri Mineral Trioksit Agregatının pH değerini etkiler mi?
Keywords: Diş Hekimliği